Three-dimensional porous current collector and preparation method and application thereof

By using the three-dimensional porous current collector Bi-NAs@Cu, the problem of poor electrochemical performance of the negative electrode-free metal sodium batteries is solved, and ultra-stable sodium deposition peeling and long cycle stability is achieved, which significantly improves the performance of the battery.

CN119447319AActive Publication Date: 2025-02-14UNIV OF SHANGHAI FOR SCI & TECH

Patent Information

Application Number
CN202411590455.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The electrochemical performance of existing negative electrode-free metal sodium batteries is not ideal enough, and there are problems such as dendrite growth, side reactions and volume expansion, resulting in low battery degradation and sodium utilization.

Method used

Using the three-dimensional porous current collector Bi-NAs@Cu, which consists of a copper substrate and vertically grown bismuth nanosheets, is prepared by deposition of bismuth ions in N,N-dimethylformamide solution and heat treatment to form a moderate thickness and Uniform honeycomb structure.

Benefits of technology

It achieves ultra-stable sodium deposition peeling performance and long cycle stability, and can cycle stably for more than 1000 hours, significantly improving the electrochemical performance of the negative electrode-free sodium metal battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447319A_ABST
    Figure CN119447319A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional porous current collector as well as a preparation method and application thereof, belongs to the technical field of a sodium metal battery current collector, and solves the problem that the electrochemical performance of a metal sodium battery without a negative electrode in the prior art is not ideal enough. The three-dimensional porous current collector comprises a copper substrate and bismuth nanosheets vertically grown on the surface of the copper substrate, wherein the copper substrate is of a net structure, and the bismuth nanosheet is of a three-dimensional honeycomb structure. The three-dimensional porous current collector provided by the invention has ultra-stable sodium deposition stripping performance and excellent long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium metal battery current collectors, and more specifically to a three-dimensional porous current collector and a preparation method and application thereof. Background Art

[0002] With the continuous development of electric vehicles and smart grids, people have shown great interest in large-scale energy storage devices. Sodium is abundant in nature, and sodium-ion batteries have become a viable energy storage solution. Among the various anode materials for sodium-ion batteries, metallic sodium has obvious advantages due to its high specific capacity, low potential, and abundant sources, making sodium metal batteries a promising candidate for high-energy applications.

[0003] However, the commercialization of sodium metal batteries is hampered by persistent challenges, including severe dendrite growth, persistent side reactions, and significant volume expansion at the electrode / electrolyte interface. The growth of sodium dendrites can lead to membrane penetration, resulting in battery short circuits. In addition, side reactions and persistent volume expansion promote the decomposition and reconstruction of the solid electrolyte interphase (SEI), exacerbating the growth of dendrites, leading to the stripping of a large amount of "dead sodium", further resulting in sodium inactivity and accelerated battery degradation. At the same time, the direct use of metallic sodium as the negative electrode may lead to excessive thickening, reduce energy density and bring potential risks.

[0004] These challenges hinder the realization of sodium metal as a high-energy density battery. In the ideal state of anode-free sodium metal battery, the utilization rate of sodium during its charge and discharge process can reach 100%. However, the requirements for materials of anode-free sodium metal battery are more stringent, corresponding to higher Coulomb efficiency values, almost no dendrites, no "dead sodium", etc., which may lead to faster capacity decay and more serious problems such as side reactions and short cycle life during actual charge and discharge. Therefore, more optimization methods are needed to regulate the electrode / electrolyte interface to improve its electrochemical performance. Summary of the invention

[0005] The present invention provides a three-dimensional porous current collector and a preparation method and application thereof, which are used to solve the problem that the electrochemical performance of a negative electrode-free metal sodium battery in the prior art is not ideal.

[0006] In a first aspect, the present invention provides a three-dimensional porous current collector, comprising a copper substrate and bismuth nanosheets vertically grown on the surface of the copper substrate; wherein the copper substrate is a mesh structure, and the bismuth nanosheets are a three-dimensional honeycomb structure.

[0007] As a possible implementation, the mesh aperture of the copper substrate is 40-50 μm; the thickness of the copper substrate is 100-150 μm; and the honeycomb aperture of the bismuth nanosheet is 50-300 nm.

[0008] In a second aspect, the present invention provides a method for preparing a three-dimensional porous current collector as described in any possible implementation of the first aspect, comprising the following steps: placing the copper substrate in an N,N-dimethylformamide solution of bismuth ions, heating at 37 to 43° C. for 11 to 13 hours to obtain a crude product; and sequentially washing and vacuum drying the crude product to obtain the three-dimensional porous current collector.

[0009] As a possible implementation manner, the cleaning agent used in the cleaning is any one of ethanol and deionized water; and / or the vacuum drying operation is vacuum drying at a temperature of 55 to 65° C. for 8 to 12 hours.

[0010] As a possible implementation manner, in the N,N-dimethylformamide solution of bismuth ions, the donor of the bismuth ions is bismuth chloride.

[0011] As a possible implementation manner, the molar ratio of the copper element of the copper substrate to the bismuth ion is 3:1.5-2.5; and / or the concentration of the organic solution of the bismuth ion is 0.018-0.022M.

[0012] As a possible implementation method, the following steps are included: placing the copper substrate in an N,N-dimethylformamide solution of bismuth chloride with a concentration of 0.02 mol / L, heating at 40°C for 12 hours to obtain the crude product; washing the crude product with ethanol, and vacuum drying it in a vacuum drying oven at 60°C for 8 hours to obtain the three-dimensional porous current collector.

[0013] In a third aspect, the present invention provides an application of a three-dimensional porous current collector described in any possible implementation of the first aspect or a three-dimensional porous current collector prepared by the preparation method described in any possible implementation of the second aspect in a negative electrode-free sodium metal battery.

[0014] As a possible implementation method, the preparation process of the negative electrode-free sodium metal battery includes the following steps: using the three-dimensional porous current collector as a current collector, assembling it with a sodium sheet, an electrolyte and a separator into a sodium-copper half-cell, and depositing sodium on the three-dimensional porous current collector according to the positive and negative electrode N / P=1 to form a composite current collector; using the composite current collector as a negative electrode, assembling it with a positive electrode, an electrolyte and a separator to obtain the negative electrode-free sodium metal battery.

[0015] As a possible implementation, the positive electrode is sodium titanium phosphate, the electrolyte is an ether electrolyte, and the diaphragm is a polypropylene diaphragm.

[0016] The present invention provides a three-dimensional porous current collector (Bi-NAs@Cu) that exhibits ultra-stable sodium deposition stripping performance and can be stably cycled for more than 1000 hours. This is because during the first electrochemical reaction, an electroplating process occurs on the electrode surface, causing the protective layer metal on the electrode surface to alloy with the electroplated sodium, thereby forming an alloy layer on the protective layer. The alloy layer on the electrode surface can also serve as a composite material that reduces sodium nucleation resistance and induces uniform deposition of sodium.

[0017] The invention provides a method for preparing a three-dimensional porous current collector. The solvent of bismuth chloride is N,N-dimethylformamide, which realizes a polymer structure with bismuth chloride through a chlorine bridge, and provides a stable and uniform electrochemical environment during the oxidation and reduction process of bismuth ions and copper, so that the bismuth nanosheets of the obtained three-dimensional porous current collector have moderate thickness, uniform and stable honeycomb distribution and moderate honeycomb pore size.

[0018] The present invention provides an application of a three-dimensional porous current collector in a negative electrode-free sodium metal battery, which exhibits ultra-stable sodium deposition stripping performance and excellent long-cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 The cross-sectional SEM images of Bi-NAs@Cu-A provided in the embodiments of the present invention, wherein (a) is a 100 μm-level SEM image and (b) is a local magnified image of a 500 nm-level SEM image.

[0021] Figure 2 The longitudinal cross-sectional SEM images of Bi-NAs@Cu-A provided in the embodiments of the present invention, wherein (a) is a local enlarged image at the 100 μm level and (b) is a local enlarged image at the 500 nm level.

[0022] Figure 3 TEM image of Bi-NAs@Cu-A provided in an embodiment of the present invention.

[0023] Figure 4 This is an XRD diagram of Bi-NAs@Cu-A provided in an embodiment of the present invention, wherein Intensity represents intensity.

[0024] Figure 5 This is a SEM image of Bi-NAs@Cu-B provided in an embodiment of the present invention.

[0025] Figure 6 This is a SEM image of Bi-NAs@Cu-C provided in an embodiment of the present invention, wherein Dimethyl sulfoxide represents dimethyl sulfoxide.

[0026] Figure 7 This is a SEM image of Bi-NAs@Cu-D provided in an embodiment of the present invention, wherein N-methyl pyrrolidone represents N-methylpyrrolidone.

[0027] Figure 8 This is a SEM image of Bi-NAs@Cu-E provided in an embodiment of the present invention, wherein Ethylene glycol represents ethylene glycol.

[0028] Fig. 9 This is a SEM image of Bi-NAs@Cu-F provided in an embodiment of the present invention, wherein Ethanol represents ethanol.

[0029] Fig.10 The half-cells made of Bi-NAs@Cu-A, Pure Cu-mesh and Pure Cu-foil provided in the embodiments of the present invention are respectively 1 mA·cm -2 and 1mAh·cm -2 The cycle performance diagram under the conditions of , where Coulombicefficiency represents the coulomb efficiency and Cycle number represents the number of cycles.

[0030] Fig.11 The half-cell made of Bi-NAs@Cu-B provided in the embodiment of the present invention is 1 mA·cm -2 and 1mAh·cm -2 The cycle performance diagram under the conditions of , where Coulombic efficiency represents the Coulombic efficiency and Cycle number represents the number of cycles.

[0031] Fig.12 The half-cell made of Bi-NAs@Cu-C provided in the embodiment of the present invention is 1 mA·cm -2 and 1mAh·cm -2 The cycle performance diagram under the conditions of , where Coulombic efficiency represents the Coulombic efficiency and Cycle number represents the number of cycles.

[0032] Fig.13 This is a cycle performance diagram of a symmetrical battery made of Bi-NAs@Cu-A provided in an embodiment of the present invention when the discharge depth is 75%, wherein Voltage represents voltage.

[0033] Fig.14 The cycle stability test results of the negative electrode-free sodium metal battery made of Bi-NAs@Cu-A and Pure Cu-mesh provided in the embodiments of the present invention are shown in Figure 1, wherein Discharge capacity represents the discharge capacity and Coulomb efficiency represents the coulomb efficiency. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In order to solve the problem that the electrochemical performance of the negative electrode-free sodium metal battery in the prior art is not ideal, the embodiment of the present invention provides a three-dimensional porous current collector preparation experiment and its morphology characterization experiment. It can be seen that the embodiment of the present invention successfully prepared the target product, and the provided three-dimensional porous current collector has a porous substrate and a three-dimensional honeycomb surface, and its thickness is about 10nm, its spacing is 50 to 300nm, and the lateral size is 100 to 500nm. Moreover, in the preparation of the three-dimensional porous current collector, when the solvent of bismuth chloride is DMSO, NMP, ethylene glycol or ethanol, the bismuth nanosheets of the obtained product all show the problems of high thickness, honeycomb shape and uneven size distribution.

[0036] Furthermore, the present invention provides an electrochemical performance test experiment of a three-dimensional porous current collector. It can be seen that Bi-NAs@Cu-A exhibits ultra-stable sodium deposition stripping performance and can be stably cycled for more than 1000 hours. Moreover, in the symmetric battery test, when the DOD is 75%, Bi-NAs@Cu-A can continue to stably cycle for more than 1000 hours and maintain a small nucleation overpotential.

[0037] Furthermore, the present invention provides an application performance test experiment of a three-dimensional porous current collector. It can be seen that at a current density of 1C, the sodium metal battery participating in Bi-NAs@Cu-A can stably cycle 267 times, confirming that Bi-NAs@Cu-A has great application potential in negative electrode-free sodium metal batteries.

[0038] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0039] Example 1

[0040] This embodiment provides an experiment for preparing a three-dimensional porous current collector.

[0041] The size is 4×4cm 2 The copper mesh was washed with dilute hydrochloric acid and deionized water in turn, and then dried to obtain copper substrate A. Bismuth chloride was dissolved in N,N-dimethylformamide (DMF) and dispersed evenly by ultrasonication for 5 minutes to form a solution A with a final concentration of 0.02 mol / L. The copper substrate A was placed in solution A, heated in a water bath at 40°C for 12 hours, taken out and washed with ethanol, and then placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours to obtain a three-dimensional porous current collector A, named Bi-NAs@Cu-A.

[0042] The size is 4×4cm 2 The copper mesh was washed with dilute hydrochloric acid and deionized water in turn, and then dried to obtain a copper substrate B. Bismuth chloride was dissolved in DMF and dispersed evenly by ultrasonication for 5 minutes to form a solution B with a final concentration of 0.02 mol / L. The copper substrate B was placed in solution B, heated in a water bath at 40°C for 24 hours, taken out and washed with ethanol, and then placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours to obtain a three-dimensional porous current collector B, named Bi-NAs@Cu-B.

[0043] The size is 1×1cm 2 The copper mesh was washed with dilute hydrochloric acid and deionized water in turn, and then dried to obtain a copper substrate C. Bismuth chloride was dissolved in dimethyl sulfoxide (DMSO) and dispersed evenly by ultrasonication for 5 minutes to form a solution C with a final concentration of 0.02 mol / L. The copper substrate C was placed in solution C, heated in a water bath at 20°C for 12 hours, taken out and washed with ethanol, and then placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours to obtain a three-dimensional porous current collector C, named Bi-NAs@Cu-C.

[0044] The size is 1×1cm 2 The copper mesh was washed with dilute hydrochloric acid and deionized water in turn, and then dried to obtain a copper substrate D. Bismuth chloride was dissolved in N-methylpyrrolidone (NMP) and dispersed evenly by ultrasonication for 5 minutes to form a solution D with a final concentration of 0.02 mol / L. The copper substrate D was placed in solution D, heated in a water bath at 20°C for 24 hours, taken out and washed with ethanol, and then placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours to obtain a three-dimensional porous current collector D, named Bi-NAs@Cu-D.

[0045] The size is 1×1cm 2The copper mesh was washed with dilute hydrochloric acid and deionized water in turn, and then dried to obtain a copper substrate E. Bismuth chloride was dissolved in ethylene glycol and dispersed evenly by ultrasonication for 5 minutes to form a solution E with a final concentration of 0.02 mol / L. The copper substrate E was placed in solution E, heated in a water bath at 20°C for 24 hours, taken out and washed with ethanol, and then placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours to obtain a three-dimensional porous current collector E, named Bi-NAs@Cu-E.

[0046] The size is 1×1cm 2 The copper mesh was washed with dilute hydrochloric acid and deionized water in turn, and then dried to obtain a copper substrate F. Bismuth chloride was dissolved in ethanol and dispersed evenly by ultrasonication for 5 minutes to form a solution F with a final concentration of 0.02 mol / L. The copper substrate F was placed in solution F, heated in a water bath at 20°C for 24 hours, taken out and washed with ethanol, and then placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours to obtain a three-dimensional porous current collector F, named Bi-NAs@Cu-F.

[0047] The size is 4×4cm 2 The copper mesh was washed with dilute hydrochloric acid and deionized water in turn and dried to serve as the current collector G, named Pure Cu-mesh.

[0048] The size is 4×4cm 2 The copper foil was washed with dilute hydrochloric acid and deionized water in turn, and then dried to serve as the current collector H, named Pure Cu-foil.

[0049] Example 2

[0050] This embodiment provides a morphology characterization experiment of a three-dimensional porous current collector.

[0051] The Bi-NAs@Cu-A prepared in Example 1 was observed by SEM and TEM morphology, and the cross-section and longitudinal section thereof were analyzed by SEM morphology at different magnifications, and the following results were obtained: Figure 1 , Figure 2 and Figure 3 The results are shown. It can be seen that the prepared three-dimensional porous current collector has a porous substrate and a three-dimensional honeycomb surface; the thickness of the bismuth nanosheet attached to the substrate is about 10nm, the honeycomb pore size is 50-300nm, and the radial length is 100-500nm. .

[0052] The Bi-NAs@Cu-A prepared in Example 1 was subjected to XRD analysis and compared with the XRD standard cards of copper and bismuth, and the following results were obtained: Figure 4 The results shown by Figure 4It can be seen that Bi-NAs@Cu-A not only has the characteristic peak of bismuth (012) but also the characteristic peak of copper (111), which further indicates that the target product was successfully prepared.

[0053] The SEM morphology of the Bi-NAs@Cu-B prepared in Example 2 was observed, and the following Figure 5 The results are shown in Figure 2. It can be seen that the bismuth nanosheets on Bi-NAs@Cu-B are thicker and the shape and size of the honeycombs are uneven.

[0054] The SEM morphology of the Bi-NAs@Cu-C prepared in Example 3 was observed, and the following Figure 6 The results are shown in Figure 2. It can be seen that the bismuth nanosheets on Bi-NAs@Cu-C are thicker and the shape and size of the honeycombs are uneven.

[0055] The SEM morphology of the Bi-NAs@Cu-D prepared in Example 4 was observed, and the following Figure 7 The results are shown in Figure 2. It can be seen that the bismuth nanosheets on Bi-NAs@Cu-D are thicker and the shape and size of the honeycombs are uneven.

[0056] The SEM morphology of the Bi-NAs@Cu-E prepared in Example 5 was observed, and the following Figure 8 The results are shown in Figure 2. It can be seen that the bismuth nanosheets on Bi-NAs@Cu-E are thicker and the shape and size of the honeycombs are uneven.

[0057] The SEM morphology of the Bi-NAs@Cu-F prepared in Example 6 was observed, and the following Fig. 9 The results are shown in Figure 2. It can be seen that the bismuth nanosheets on Bi-NAs@Cu-F are thicker and the shape and size of the honeycombs are uneven.

[0058] Example 3

[0059] This embodiment provides an electrochemical performance test experiment of a three-dimensional porous current collector.

[0060] The current collector to be tested is punched and cut into electrode sheets with a diameter of not less than 10 mm as the working electrode, and the sodium sheet is used as the negative electrode to assemble the sodium||copper half-cell. The sodium||copper half-cell is used as the working electrode in the symmetric cell and full cell test by using the composite sodium metal negative electrode formed by the electrodeposition method, and the 1M diethylene glycol dimethyl ether solution of sodium hexafluorophosphate is used as the electrolyte; the working electrode, the separator (Celgard PP 2325) and the electrolyte are assembled into a battery device. In this example, Bi-NAs@Cu-A~Bi-NAs@Cu-F, Pure Cu-mesh and Pure Cu-foil in Example 1 are used as the current collectors to be tested, respectively, to assemble half-cells A~H, and symmetric cells A~H are assembled using half-cells A~H.

[0061] For half-cell A, half-cell G and half-cell H, the -2 and 1mAh·cm -2 The asymmetric battery was tested under the conditions of Fig.10 The results are shown. It can be seen that Bi-NAs@Cu-A exhibits ultra-stable sodium deposition stripping performance and can be stably cycled for more than 1000 hours. This is because during the first electrochemical reaction, the electroplating process occurs on the electrode surface, causing the protective layer metal on the electrode surface to alloy with the electroplated sodium, thereby forming an alloy layer on the protective layer; the alloy layer on the electrode surface can also serve as a composite material that reduces the sodium nucleation resistance and induces uniform deposition of sodium. Pure Cu-foil also exhibits certain sodium deposition stripping performance, but it is far inferior to Bi-NAs@Cu. At the same time, Pure Cu-mesh exhibits unstable and highly fluctuating coulombic efficiency, indicating that its sodium deposition stripping performance is poor, which may be caused by the formation of dendrites during the process.

[0062] For half cell B at 1 mA·cm -2 and 1mAh·cm -2 The asymmetric battery was tested under the conditions of Fig.11 The results are shown. It can be seen that the coulombic efficiency of thicker and non-uniform bismuth nanosheets fluctuates greatly. This is because a large number of dendrites are formed during the deposition and stripping process, which causes the nanosheet structure to collapse during the charge and discharge process, showing poor sodium deposition and stripping performance.

[0063] For half-cell C at 1 mA·cm -2 and 1mAh·cm -2 The asymmetric battery was tested under the conditions of Fig.12 The results are shown. It can be seen that the Coulomb efficiency of bismuth nanosheets with uneven sizes fluctuates greatly. This is because a large number of dendrites are formed during the deposition and stripping process, which causes the nanosheet structure to collapse during the charge and discharge process, showing poor sodium deposition and stripping performance.

[0064] Symmetrical battery A was tested, and the cycle performance comparison chart when the depth of discharge (DOD) was 75% is as follows: Fig.13 As shown, when the DOD is 75%, Bi-NAs@Cu-A can be continuously and stably cycled for more than 1000 hours and maintain a small nucleation overpotential.

[0065] Example 4

[0066] This embodiment provides an application performance testing experiment of a three-dimensional porous current collector.

[0067] The Bi-NAs@Cu-A and Pure Cu-mesh of Example 1 were used as current collectors, sodium titanium phosphate as the positive electrode, an ether electrolyte as the electrolyte, and PP (polypropylene) as the separator. Negative electrode-free sodium metal batteries were assembled respectively, and the cycle stability of the two sodium metal batteries was tested. The results are as follows: Fig.14 The results shown. Fig.14 It can be seen that at a current density of 1C, the sodium metal battery participating in Bi-NAs@Cu-A can stably cycle 267 times, confirming that Bi-NAs@Cu-A has great application potential in negative electrode-free sodium metal batteries.

[0068] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0069] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A three-dimensional porous current collector, characterized in that: It comprises a copper substrate and bismuth nanosheets vertically grown on the surface of the copper substrate; Wherein, the copper substrate is a mesh structure, and the bismuth nanosheets are a three-dimensional honeycomb structure.

2. The three-dimensional porous current collector according to claim 1, characterized in that: The mesh aperture of the copper substrate is 40-50 μm; the thickness of the copper substrate is 100-150 μm; The honeycomb pore size of the bismuth nanosheet is 50-300 nm.

3. The method for preparing the three-dimensional porous current collector according to any one of claims 1 to 2, characterized in that: The following steps are involved: placing the copper substrate in a bismuth ion N,N-dimethylformamide solution, and heating at 37-43° C. for 11-13 hours to obtain a crude product; The crude product is sequentially washed and vacuum dried to obtain the three-dimensional porous current collector.

4. The preparation method according to claim 3, characterized in that: The cleaning agent used in the cleaning is any one of ethanol and deionized water; And / or, the vacuum drying operation is vacuum drying at a temperature of 55 to 65° C. for 8 to 12 hours.

5. The preparation method according to claim 3, characterized in that: In the N,N-dimethylformamide solution of bismuth ions, the donor of the bismuth ions is bismuth chloride.

6. The preparation method according to claim 3, characterized in that: The molar ratio of the copper element of the copper substrate to the bismuth ion is 3:1.5-2.5; And / or, the concentration of the organic solution of bismuth ions is 0.018-0.022M.

7. The preparation method according to claim 3, characterized in that: The following steps are involved: placing the copper substrate in a 0.02 mol / L bismuth chloride N,N-dimethylformamide solution, and heating at 40° C. for 12 h to obtain the crude product; The crude product was washed with ethanol and then vacuum dried in a vacuum drying oven at 60° C. for 8 h to obtain the three-dimensional porous current collector.

8. Use of the three-dimensional porous current collector according to any one of claims 1 to 2 or the three-dimensional porous current collector prepared by the preparation method according to any one of claims 3 to 7 in a negative electrode-free sodium metal battery.

9. The use according to claim 8, characterized in that: The preparation process of the negative electrode-free sodium metal battery comprises the following steps: The three-dimensional porous current collector is used as a current collector, assembled with a sodium sheet, an electrolyte and a separator into a sodium-copper half-cell, and sodium is deposited on the three-dimensional porous current collector according to the positive and negative electrode N / P=1 to form a composite current collector; The composite current collector is used as the negative electrode and assembled with the positive electrode, electrolyte and separator to obtain the negative electrode-free sodium metal battery.

10. The use according to claim 9, characterized in that: The positive electrode is sodium titanium phosphate, the electrolyte is an ether electrolyte, and the diaphragm is a polypropylene diaphragm.

Citation Information

Patent Citations

  • Bismuth / carbon nano array negative electrode material and preparation method thereof, sodium ion battery and preparation method thereof

    CN117174851A

  • Preparation method and application of ordered silver nanoparticle-bismuth nanosheet-copper mesh array

    CN117696911A

  • Composite current collector, preparation method thereof and battery

    CN118136851A

Cited By

  • Current collector for a negative electrode-free battery, method for manufacturing the same, and sodium-ion battery

    CN122913503A